2005
DOI: 10.4012/dmj.24.428
|View full text |Cite
|
Sign up to set email alerts
|

Color and Translucency of Resin Composites for Layering Techniques

Abstract: The purpose of this study was to evaluate the colors of resin composites used for the layering technique, as well as the translucency at various thickness.For the purpose of calculating the translucency parameter (TP) , black and white backings were used to evaluate the CIELAB parameters of Filtek Supreme (3M) and Gradia Direct (GC) disks of various thicknesses (0.5, 1.0, 2.0, 3.0 and 4.0 mm) and of three different shades (enamel-shade, body-shade, and opaque-shade) . As for the color of each shade, it was eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
82
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(94 citation statements)
references
References 13 publications
(3 reference statements)
4
82
0
Order By: Relevance
“…As the translucency of a material increases, more light is absorbed until the relevant portion of the light is reflected. The different translucencies of dental materials have been investigated by several studies using the translucency parameter (TP) [9][10][11][12][13][14][15][16][17][18][19]. In all of the referenced studies, the TP was determined by measuring the values for L* (lightness), a* (redgreen chromatic coordinates), b* (yellow-blue chromatic coordinates) over W -background (values determined using a white background) and B -background (values determined using a black background) and then substituting them into the following equation:…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the translucency of a material increases, more light is absorbed until the relevant portion of the light is reflected. The different translucencies of dental materials have been investigated by several studies using the translucency parameter (TP) [9][10][11][12][13][14][15][16][17][18][19]. In all of the referenced studies, the TP was determined by measuring the values for L* (lightness), a* (redgreen chromatic coordinates), b* (yellow-blue chromatic coordinates) over W -background (values determined using a white background) and B -background (values determined using a black background) and then substituting them into the following equation:…”
Section: Introductionmentioning
confidence: 99%
“…The TP is closely correlated in inverse proportion to the thickness of the sample [9,10,13,15,20]. Furthermore, the shade of a material can lead to its having a different TP [10,11,14,21]. The translucency of enamel is always higher than that of dentine [9,14].…”
Section: Introductionmentioning
confidence: 99%
“…The maximum thickness of 4.0 mm was described on a study by Kamishima and colleagues, who reported that enamel composite resins were not influenced by the background contrast at this thickness (5). To match tooth color, various shades of yellow and gray pigments are blended to white base material of traditional resin composites.…”
Section: Translucency Of Natural Teethmentioning
confidence: 99%
“…The layering technique attempts to replace dentin and enamel by placing a more translucent layer over a more opaque layer of resin composite to create a perception of depth from within the restoration. 7 However, studies have reported poor compatibility of resin composites of identical shade designation between pairs of shades, 8,9 and the color of the restoration was influenced by the optical properties of the enamel layer as well as those of the dentin layer. 7,10 On the other hand, incorporation of enamel and translucent layers on resin overlays increased curing light penetration through layered resin overlays.…”
Section: Introductionmentioning
confidence: 99%
“…7 However, studies have reported poor compatibility of resin composites of identical shade designation between pairs of shades, 8,9 and the color of the restoration was influenced by the optical properties of the enamel layer as well as those of the dentin layer. 7,10 On the other hand, incorporation of enamel and translucent layers on resin overlays increased curing light penetration through layered resin overlays. 11 Higher curing light penetration could enhance the light curing of DCRC beneath the resin overlays.…”
Section: Introductionmentioning
confidence: 99%